A Dual Targeting Drug Delivery System for Penetrating Blood-Brain Barrier and Selectively Delivering siRNA to Neurons for Alzheimer's Disease Treatment - Zhang, Chi; Gu, Zhichun; Shen, Long; Liu, Xianyan; Lin, Houwen (Current Pharmaceutical Biotechnology, 2017)
Background: Alzheimer's disease (AD) is one of most serious threats to human beings, however, the treatment is hindered by blood-brain barrier and poor intra-brain cell selectivity. Methods: In this study, we developed a novel dual targeting drug delivery system by modification of NL4 peptide and apolipoprotein A-I (ApoA-I) onto dendrimer particles that may efficiently deliver siRNA into neuron cells to down-regulate BACE1 and inhibit Aβ formation. The constructed ANNP/ siRNA was approximately 79.26 nm with a spherical structure and a zeta potential of 3.53 mV. At N/P ratio of 10, the siRNA could be completely packaged into particles to avoid degradation by RNAase. Results: In vitro, the modification with ApoA-I considerably increased bEnd.3 cell uptake and NL-4 considerably increased PC12 cell uptake. As a result, ANNP/siRNA showed higher uptake in both the cells. In addition, ANNP/siRNA could efficiently penetrate through bEnd.3 monolayers, which was 2.4-fold higher than unmodified complexes. In PC12 cells, the ANNP/siRNA could escape from endosomes and transport into cytoplasm after 8 h incubation, resulting in 87.5% BACE1 gene knockdown capacity, which was better than PEI. Additionally, the particles showed low cytotoxicity to both bEnd.3 and PC12 cells. Conclusion: In conclusion, this study preliminarily demonstrated that ApoA-I and NL4 dual modified dendrimer nanoparticles were efficient carriers for siRNA delivery to AD bearing brain.
Keywords: ALzheimer' s disease